Determinants of non-adherence to adjuvant endocrine treatment in women with breast cancer: the role of comorbidity - Wulaningsih, W. (Breast Cancer Res Treat, 2018)
PURPOSE: To examine factors associated with non-adherence during 5 years of endocrine treatment, including the possible influence of comorbidity burden and specific medical conditions. METHODS: From all women diagnosed with stage I–III, ER-positive breast cancer in Stockholm-Gotland, Uppsala–Örebro and Northern Sweden between 2006 and 2009, we included 4645 women who had at least one dispensation of tamoxifen or aromatase inhibitors (AIs) and 5 years of follow-up without distant recurrence. A medical possession ratio of < 80% was used to define non-adherence. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of non-adherence. RESULTS: During follow-up, 977 (21%) women became non-adherents. Non-adherence was associated with greater comorbidity burden assessed by Charlson comorbidity index (CCI) during follow-up (OR 1.43; 95% CI 1.08–1.88 for ≥ 2 additional scores compared to 0), pre-diagnostic HRT use (OR 1.99; 1.58–2.49), not married (OR 1.42; 1.23–1.64), high educational level (OR 1.25; 1.02–1.53 compared to lowest level), and use of symptom-relieving drugs. HER-2 positivity (OR 0.61; 0.45–0.81) and adjuvant chemotherapy (OR 0.42; 0.35–0.52) were associated with lower odds of non-adherence. Similar patterns were observed for the presence of lymph node metastasis, higher tumour grade, and use of AIs compared to tamoxifen. Myocardial infarction and chronic pulmonary disease was suggested as leading conditions associated with non-adherence in women with increasing CCI. CONCLUSION: We identified subgroups of women with breast cancer at increased risk of non-adherence. Our findings related to comorbidity suggest the importance of focusing on the presence of specific co-existing conditions when monitoring adherence.